Volatilization of ammonia from conventional sources of nitrogen and compacted urea under controlled conditions - Souza, Juscelio Ramos de [UNESP]; Lemos, Leandro Borges [UNESP]; Leal, Fabio Tiraboschi [UNESP]; Magalhaes, Riscelly Santana [UNESP]; Ribeiro, Bruno Neves [UNESP]; Cabral, Wagner Francisco; De Gissi, Luciano (Univ Federal Rural Pernambuco, 2020)
Urea is the most used nitrogen fertilizer in tropical agriculture, but when applied to the soil surface, it can promote nitrogen (N) losses by volatilization of ammonia (NH3). The present study aimed to evaluate, under controlled laboratory conditions, the N-NH3 losses from conventional N sources and compacted urea. Fertilizers were applied on the surface of a eutrophic Red Latosol of clayey texture (Oxisol), previously moistened to 60% of its maximum water-retention capacity. Conduction of the experiment was in a completely randomized design with six replicates. The treatments were four N sources in doses equivalent to 100 kg ha(-1) of N (urea, urea + N-(N-butyl) thiophosphoric triamide (NBPT), ammonium nitrate and urea compacted with additives and polymers), and the additional control groups (soil with no fertilizer and empty chamber). We evaluated the N-NH3 losses by volatilization for a period of 20 days with the aid of hermetically sealed chambers. The results demonstrated the importance of using compacted urea for reducing nitrogen losses via volatilization. These results suggest that choosing the N source can reduce its volatilization and thus improve the harnessing of N from the nitrogen fertilization, when performed with a urea basis.
Keywords: nitrogen fertilization; N-NH3 losses; nutritional efficiency